Interactive Student Worksheets Based on Discovery Learning in Science Subjects for Grade V Elementary School - Ni Putu Mira Adella Rohalina Putri; I Wayan Wiarta; Didith Pramunditya Ambara (Universitas Pendidikan Ganesha, 2025)
Science learning in elementary schools is often still conventional, where students are less actively involved in the learning process. One of the causes is the limited teaching materials that support independent exploration and discovery of concepts. This study aims to develop and analyze the effectiveness of interactive Student Worksheets (LKPD) based on Discovery Learning on the material of Light and Its Properties in grade V of elementary school. This type of research is development research. The development of LKPD uses the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subjects of the study were 27 grade V students. The method used is development research with instruments in the form of questionnaires and tests. Data analysis techniques include qualitative, quantitative and inferential descriptive analysis. The results of the study indicate that interactive LKPD is effective in improving students' understanding of concepts and learning motivation. The implication of this study is that the use of interactive teaching materials can increase student involvement in science learning and help teachers implement discovery-based learning more effectively.